2021
DOI: 10.1088/1361-6560/ac299a
|View full text |Cite|
|
Sign up to set email alerts
|

EFNet: evidence fusion network for tumor segmentation from PET-CT volumes

Abstract: Precise delineation of target tumor from positron emission tomography-computed tomography (PET-CT) is a key step in clinical practice and radiation therapy. PET-CT co-segmentation actually uses the complementary information of two modalities to reduce the uncertainty of single-modal segmentation, so as to obtain more accurate segmentation results. At present, the PET-CT segmentation methods based on fully convolutional neural network (FCN) mainly adopt image fusion and feature fusion. The current fusion strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In the HECKTOR dataset, where the axial size of PET and CT images is different, some methods resample PET/CT images to 1×1×1 mm in each direction and crop them to 144×144×144 size ( 23 , 24 , 35 ). For the STS dataset, where the PET axial size is 128×128, and the CT axial size is 256×256, some works ( 36 , 37 ) resize CT to match PET size to 128×128, or linearly interpolate PET to CT size ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the HECKTOR dataset, where the axial size of PET and CT images is different, some methods resample PET/CT images to 1×1×1 mm in each direction and crop them to 144×144×144 size ( 23 , 24 , 35 ). For the STS dataset, where the PET axial size is 128×128, and the CT axial size is 256×256, some works ( 36 , 37 ) resize CT to match PET size to 128×128, or linearly interpolate PET to CT size ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the similarities between OPC and NPC, we also compared the segmentation methods for NPC. In addition, we compared with other tumor segmentation methods based on FDG-PET/CT datasets (Diao et al 2021, Fu et al 2021 as well as some general medical image segmentation methods (Isensee et al 2021, Valanarasu and Patel 2022, As shown in table 1, excluding nnUNet (Isensee et al 2021), the proposed method was superior to all other methods in terms of DSC, precision, and sensitivity, indicating that our method had good segmentation performance and could effectively improve the accuracy of tumor segmentation. Furthermore, the proposed model had poor performance in the HD95 segmentation metric, indicating that the proposed method was not sensitive to tumor boundary segmentation.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…The models performed well on photo-based datasets, which have certain clinical application values in specific fields. Compared with the methods proposed by Fu et al (2021), Isensee et al (2021), andDiao et al (2021), our method had relatively low requirements for the experimental environment and equipment. Compared with other comparison methods, the proposed method had relatively high segmentation performance.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
See 2 more Smart Citations